Mapeamento tecnológico da uncaria tomentosa. - Simões, Evelyne Rolim Braun (2017)
In the last years, the world has undergone a revolution, impacting in the political, economic, technological and social life, and these formed a gap among countries that have not reached the desired level of development and the so-called "first world". However, Brazil has developed innovative initiatives, so that, although still considered a "developing country" is not condemned to perpetuate this situation. We need to know what are the ways that will allow our economy to be more competitive in global markets, establishing new and better levels of development for the country and that will effectively contribute to sustainability of our economy. The research proposes a technological forecasting on Uncaria tomentosa, a priority medicinal plant indicated by the Ministry of Health in order to develop of herbal medicine, analyzing scientific study previously performed and / or patented. Therefore, in the methodology used databases were accessed, such as Web of Science, Derwent Innovations Index and Alice web. Graphical analyzes were performed using VantagePoint® software and Microsoft Excel. In the analysis, it was possible to observe the increasing volume of scientific studies carried out in the world and particularly in Brazil. The articles began to be published in 1984 and the peak occurred in 2005 in the different areas of the sciences, such as chemistry, toxicology, pharmacology, and Brazil is responsible for the largest volume of publications. On the other hand, the countries with the largest patent assignees were the United States, China, Japan and Austria. There was a growing correlation of publications and patent deposits between 1980 and 2006. On the other hand, from 2007 this correlation is not directly proportional. It is important to observe that protected technologies reached the market earlier in the countries where protection was provided, highlighting the United States. Therefore, it is possible to affirm the technological potential for the phytotherapeutic development of the Uncaria tomentosa plant to be incorporated by the public pharmaceutical industries and distributed in the SUS system.